Computing Optical Properties of Photonic Crystals by Using Multilayer Perceptron and Extreme Learning Machine - Da Silva Ferreira, Adriano; Malheiros-Silveira, Gilliard Nardel [UNESP]; Hernandez-Figueroa, Hugo Enrique (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In this paper, dispersion relations (DRs) of photonic crystals (PhCs) are computed by multilayer perceptron (MLP) and extreme learning machine (ELM) artificial neural networks (ANNs). Bi- and tri-dimensional optimized structures presenting distinct DRs and photonic band gaps (PBGs) were selected for case studies. Optical properties of a set of PhCs with similar geometries and different dimensions were calculated by an electromagnetic solver in order to provide input data for ANN training and testing. We demonstrate that simple- and fast-training ANN models are capable of providing accurate DRs' curves in a very short time.
Keywords: Dispersion relation; extreme learning machine; multilayer perceptron; photonic band gap; photonic crystal